PERAN PENGELOLA TEKNIS DALAM PENGENDALIAN PROYEK PADA KEGIATAN PEMBANGUNAN KONSTRUKSI TAMAN PAVING DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KABUPATEN MUKOMUKO - Mei sahputra; INSANNUL KAMIL (Inersia: Jurnal Teknik Sipil, 2024)
In the infrastructure development process, project control is required with the aim of minimizing all deviations during the development process. In project control, all activities are regulated so that they function optimally, so that implementation is on time according to the time schedule and produces work according to planning. The type and type used in this research is Descriptive Qualitative, namely research using a case study method or approach. This research focuses intensively on one particular object and studies it as a case. In the paving park construction activities of the Mukomuko Regency Public Housing and Settlement Area Service, the role of the technical manager is very important, especially in controlling time, quality, costs and security and safety in work, this is very necessary so that the development objectives are achieved.